APPLICATION OF CIMFACTORY SOFTWARE TOWARDS IMPROVEMENT OF THE PRODUCTION FLOOR LAYOUT IN A MANUFACTURING COMPANY (Jurnal Mekanikal, 2018)
The aim of this study is to help in improving the plant layout of amanufacturing company. The objective is to redesign a new layout inorder to improve the productivity. Industrial Engineering techniqueswill be implemented to identify the entire problem, which occurs in theproduction floor. After the main problem has been identified,CIMFactory simulation software that includes FactoryCAD andFactoryFLOW will be used to generate result reports. Criticalanalysis will be done based on the reports and the best alternativelayout will be suggested to the company's management for futuredevelopment.
Keywords: Keywords